Docosahexaenoic acid in the treatment of rheumatoid arthritis: A double-blind, placebo-controlled, randomized cross-over study with microalgae vs. sunflower oil. Issue 2 (April 2018) - Dawczynski, C.; Dittrich, M.; Neumann, T.; Goetze, K.; Welzel, A.; Oelzner, P.; Völker, S.; Schaible, A.M.; Troisi, F.; Thomas, L.; Pace, S.; Koeberle, A.; et al.
Summary: The potential of fish or fish oil as supplier for eicosapentaenoic acid (EPA, C20:5n3) and docosahexaenoic acid (DHA, C22:6n3) for reducing cardiovascular risk factors and supporting therapy of chronic inflammatory diseases, has been investigated intensively, but our knowledge about the physiological effects of the individual compounds EPA and DHA are limited. Study design: In this double-blind pilot study, thirty-eight patients with defined RA were allocated to consume foods enriched with microalgae oil from Schizochytrium sp. (2.1 g DHA/d) or sunflower oil (placebo) for 10 weeks (cross-over), maintaining the regular RA medication during the study. Results: In contrast to placebo, the daily consumption of DHA led to a decline in the sum of tender and swollen joints (68/66) from 13.9 ± 7.4 to 9.9 ± 7.0 (p = 0.010), total DAS28 from 4.3 ± 1.0 to 3.9 ± 1.2 (p = 0.072), and ultrasound score (US-7) from 15.1 ± 9.5 to 12.4 ± 7.0 (p = 0.160). The consumption of placebo products caused an increase of the n-6 PUFA linoleic acid and arachidonic acid (AA) in erythrocyte lipids (EL, p < 0.05). The amount of DHA was doubled in EL of DHA-supplemented patients and the ratios of AA/EPA and AA/DHA dropped significantly. We speculate that the production of pro-inflammatory/non-resolving AA-derived eicosanoids might decrease in relation to anti-inflammatory/pro-resolving DHA- and EPA-derived lipid mediators. In fact, plasma concentrations of AA-derived thromboxane B2 and the capacity of blood to convert AA to the pro-inflammatory 5-lipoxygenase product 5-hydroxyeicosatetraenoic acid were significantly reduced, while levels of the DHA-derived maresin/resolvin precursors 14-/17-hydroxydocosahexaenoic acid significantly increased due to DHA supplementation. Conclusion: The study shows for the first time that supplemented microalgae DHA ameliorates disease activity in patients with RA along with a shift in the balance of AA- and DHA-derived lipid mediators towards an anti-inflammatory/pro-resolving state.